Conceptualizing bullying in adult professional football: A phenomenological exploration. (May 2021) - Newman, James A.; Warburton, Victoria E.; Russell, Kate
Abstract: Objectives: The aim of this study was to gain an in-depth insight into male professional footballers' perception of the concept of bullying and to explore the essences of this behavior within this context. Design and Method: Semi-structured interviews were conducted with 18 adult male professional football players in the UK. Data were analyzed in accordance with the principles of Interpretative Phenomenological Analysis. Results: Participants highlighted that key themes within Olewus' (1993) seminal definition of bullying are relevant to professional football such as repetition, power, abuse and harm doing. Notably, there were variations in footballers' views of the constituents of these themes which were explained by divergent perceptions of how the football context shaped these components of bullying. It was evident however, that certain common elements of the football environment, such as its inherent masculinity, identity conforming nature and authoritarianism helped to contextualize the players' conceptualizations of bullying. Conclusions: While some of the identified themes mirrored classic definitions of bullying, this concept was articulated in an individually nuanced, context dependent fashion. These findings advance bullying literature by demonstrating how professional football shapes perceptions of this concept, while highlighting the importance of contextually tailored intervention program to address bullying. Highlights: This study provides an initial conceptualization of bullying in professional football. Bullying in football is an individually experienced, context dependent concept. The male professional football context shapes the key essences of bullying. Bullying is legitimized until the victim displays an emotional effect. Education programs need to be tailored to the individual football organization.